1, 1/2x-1 + 3/12x-8=2/3x-2 2, 3/x+3 – 1/x-2=5/2x+6 3, 4/x-2 + x/x+1=x^2-2/x^2-x-2 4, x/x^2-1 + 3/x^2-2x-3=x/x^2-4x+3

Question

1, 1/2x-1 + 3/12x-8=2/3x-2
2, 3/x+3 – 1/x-2=5/2x+6
3, 4/x-2 + x/x+1=x^2-2/x^2-x-2
4, x/x^2-1 + 3/x^2-2x-3=x/x^2-4x+3

in progress 0
Amara 4 tuần 2021-08-18T22:44:21+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T22:46:02+00:00

    1,1/2x-1+3/12x-8=2/3x-2

    =1/2x-1 +3/4(3x-2)=2/3x-2

    =1.4(3x-2)+3.(2x-1)/4.(3x-2)(2x-1)=2.4.(2x-1)/4.(3x-2)(2x-1)

    =12x-8+6x-3=16x-8

    =x=3

    2,3/x+3-1/2x-1=5/2x+6

    = 3/x+3-1/x-2=5/2(x+3)

    =3.2.(x-2)-1.2.(x+3)/2.(x+3)(x-2)=5.(x-2)/2.(x+3)(x-2)

    =6x-12-2-6x=5x-10

    =-5x=4

    =x=-4/5

    3,4/x-2+x/x+1=x^2-2/x^2-4x+3

    =4(x+1)+x(x-2)/(x+1)(x-2)=x^2/(x+1)(x-2)

    =4x+4+x^2-2x=x^2

    =x=-2

    Giải thích các bước giải:

     

    0
    2021-08-18T22:46:16+00:00

    `1, 1/2x-1+3/12x-8=2/3x-2`

    `=1/2x-1 +3/4(3x-2)=2/3x-2`

    `=1.4(3x-2)+3.(2x-1)/4.(3x-2)(2x-1)=2.4.(2x-1)/4.(3x-2)(2x-1)`

    `=12x-8+6x-3=16x-8`

    `x=3`

    `2, 3/x+3-1/2x-1=5/2x+6`

    `= 3/x+3-1/x-2=5/2(x+3)`

    `= 3.2.(x-2)-1.2.(x+3)/2.(x+3)(x-2)=5.(x-2)/2.(x+3)(x-2)`

     `= 6x-12-2-6x=5x-10`

    `=-5x = 4`

    `=x=-4/5`

    `3, 4/x-2+x/x+1=x^2-2/x^2-4x+3`

    `=4(x+1)+x(x-2)/(x+1)(x-2)=x^2/(x+1)(x-2)`

    `=4x+4+x^2-2x=x^2`

    `=x=-2`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )